[ARTÍCULO RETRACTADO PARCIALMENTE] Perspectiva de género en la profesión jurídica: revisión de la actuación de los colegios de abogados en casos de violencia de género relacionados con el ejercicio profesional - Constantino Caycho, Renato Antonio (Pontificia Universidad Católica del Perú, 2026)
This article critically examines the ways in which lawyers perpetuate situations of gender-based violence through their professional practice. To this end, it will clarify how various professional disciplinary bodies have acted in Peru. We will begin by explaining the concept of gender-based violence and its connection to the actions of lawyers, with particular reference to the recognitionof judicial harassment as part of this form of violence. Then, we will elaborateon the context and significance of the amendment made to the legislation on gender-based violence that recognized judicial harassment. Following this, we will address the stance of the Peruvian legal profession regarding gender issues. Additionally, a structured framework will be proposed to assess disciplinary cases in the context of gender-based violence. Subsequently, a specific case will be meticulously analyzed involving the prolonged legal ordeal experienced by a victim of judicial harassment, and we will evaluate cases in which Peruvian bar associations have sanctioned their members for situations that can be understood as gender-based violence. In this regard, aside from mentioning the measures imposed against the accused, this article focuses on scrutinizing the responses of the various bodies that govern legal professionals in Peru in this evolving aspect of gender-based violence. Finally, the conclusions will encompass reflections on the implications for legal ethics and gender justice within the Peruvian legal system.

Este artículo examina críticamente la forma en que los abogados perpetúan situaciones de violencia de género a través de su ejercicio profesional. Para ello, se explicará la forma en que los diferentes órganos colegiados de disciplina profesional han actuado en el Perú. Iniciaremos explicando el concepto de violencia de género y su vinculación con la actuación de los abogados, con especial referencia al reconocimiento del acoso judicial como parte de dicha forma de violencia. Luego, se explicará el contexto y valor de la enmienda que reconoció el acoso judicial, para abordar después la postura de la abogacía peruana existente en materia e género. También se propone un marco estructurado para evaluar los casos disciplinarios en el contexto de la violencia de género. Posteriormente, se analizarán los casos en los cuales los colegios de abogados peruanos hayan sancionado a sus miembros por casos que se pueden entender como violencia de género. En este sentido, aparte de mencionar las medidas impuestas en contra del acusado, el presente artículo se centra en el escrutinio de las respuestas de los diversos organismos que rigen a los profesionales del derecho en el Perú en esta faceta cambiante de la violencia de género. Finalmente, las conclusiones abarcan reflexiones sobre las implicancias para la ética jurídica y la justicia de género en el ordenamiento jurídico peruano.
[PARTIALLY RETRACTED ARTICLE] Gender Perspective in the Legal Profession: Review of the Performance of the Bar Associations in Cases of Gender Violence Related to Professional Practice
Keywords: Artículo Retractado Parcialmente; https://purl.org/pe-repo/ocde/ford#5.05.01